2018
DOI: 10.1111/jocd.12744
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of therapeutic effects of conventional and liposomal form of 4% topical hydroquinone in patients with melasma

Abstract: This study shows that liposomal hydroquinone has a significant therapeutic effect on melasma, but we did not observe any superiority in comparison with the conventional method. Therefore, it can be considered in the treatment protocol of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The patients were randomly allocated to the conventional hydroquinone 4% and liposomal hydroquinone 4% groups and the melasma severity was assessed through the MASI score at defined time points. The findings of the study indicated that although the liposomal hydroquinone 4% was efficient in melasma management and could induce a significant reduction in MASI score, however, no superiority was obvious in comparison to the conventional hydroquinone cream ( Taghavi et al, 2019a ).…”
Section: Clinical Outcomes Of Pharmacotherapymentioning
confidence: 83%
See 1 more Smart Citation
“…The patients were randomly allocated to the conventional hydroquinone 4% and liposomal hydroquinone 4% groups and the melasma severity was assessed through the MASI score at defined time points. The findings of the study indicated that although the liposomal hydroquinone 4% was efficient in melasma management and could induce a significant reduction in MASI score, however, no superiority was obvious in comparison to the conventional hydroquinone cream ( Taghavi et al, 2019a ).…”
Section: Clinical Outcomes Of Pharmacotherapymentioning
confidence: 83%
“…The obtained MASI scores from this plot study indicated appreciable therapeutic effectiveness of liposomal hydroquinone in comparison to the conventional hydroquinone cream ( Banihashemi et al, 2015a ). Results of another study indicated that although the therapeutic effect of hydroquinone in melasma treatment was preserved after encapsulation in liposomes, however, no significant superiority was observed in comparison to the conventional cream ( Taghavi et al, 2019b ).…”
Section: New Approaches In Melasma Pharmacotherapymentioning
confidence: 99%
“…Multiple RCTs have been conducted, comparing HQ creams (of different percentages) with several topical agents, and variable results have been reported. [ 33 34 35 36 37 38 39 40 41 42 43 44 ] HQ is one of the most effective therapies for melasma, when compared with other agents. However, TCCs and 3% Rumex occidentalis (RO) cream score higher when a head-to-head comparison is performed.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that liposomal HQ cream was not found to be better than the conventional HQ cream, in terms of effectiveness in an Iranian RCT published in 2019. [ 41 ]…”
Section: Discussionmentioning
confidence: 99%
“…La HQ tópica sigue siendo el tratamiento más estudiado, por su excelente perfil de seguridad y efectividad, en el tratamiento del melasma. El estudio de Taghavi et al [19] mostró que la HQ en fórmula liposomal es igual de efectiva que la fórmula tradicional, aunque presenta menos efectos secundarios sobre la piel. La triple terapia combinada (TCC) continúa siendo el tratamiento más efectivo, aunque se han estudiado múltiples variaciones de su formulación original para disminuir los efectos adversos.…”
Section: Discussionunclassified